2000
DOI: 10.1378/chest.117.4.984
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lung Parenchymal Destruction on the Different Indexes of the Methacholine Dose-Response Curve in COPD Patients

Abstract: Study objectives: The interpretation of nonspecific bronchial provocation dose-response curves in COPD is still a matter of debate. Bronchial hyperresponsiveness (BHR) in patients with COPD could be influenced by the destruction of the parenchyma and the augmented mechanical behavior of the lung. Therefore, we studied the interrelationships between indexes of BHR, on the one hand, and markers of lung parenchymal destruction, on the other. Patients and methods: COPD patients were selected by clinical symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In some studies, the correlation between inflammatory markers like exhaled nitric oxide or sputum eosinophils and the PC 20 has been weak, but others have shown that the more severe the airway inflammation, the higher the rate of BHR 36,37. In addition, no functional indexes evaluating the lung parenchyma structure like pressure-volume curves or diffusion capacity (DL, CO ) have been related to BHR, which suggests that BHR is more closely related to airway abnormalities (inflammation and lumen reduction) in COPD patients 38. However, no differences have been observed between BHR in patients with chronic bronchitis and those with emphysema 39…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the correlation between inflammatory markers like exhaled nitric oxide or sputum eosinophils and the PC 20 has been weak, but others have shown that the more severe the airway inflammation, the higher the rate of BHR 36,37. In addition, no functional indexes evaluating the lung parenchyma structure like pressure-volume curves or diffusion capacity (DL, CO ) have been related to BHR, which suggests that BHR is more closely related to airway abnormalities (inflammation and lumen reduction) in COPD patients 38. However, no differences have been observed between BHR in patients with chronic bronchitis and those with emphysema 39…”
Section: Discussionmentioning
confidence: 99%
“…One recent report in smoking subjects with COPD shows that indices of BHR are not related to measures of impairment of the lung parenchyma structure, as determined by pressure-volume curves and carbon monoxide diffusion (77). This may suggest that BHR in smoking COPD patients is determined by airway pathology rather than parenchymal impairment (77). Another study has demonstrated that the presence of BHR to AMP in subjects with COPD is associated with increased numbers of CD8ϩ T cells in the lamina propria in the large airways and with higher eosinophil counts in induced sputum samples (78).…”
Section: Is Airway Inflammation Associated With Responsiveness Of Thementioning
confidence: 95%
“…One recent report in smoking subjects with COPD shows that indices of BHR are not related to measures of impairment of the lung parenchyma structure, as determined by pressure-volume curves and carbon monoxide diffusion (77). This may suggest that BHR in smoking COPD patients is determined by airway pathology rather than parenchymal impairment (77).…”
Section: Is Airway Inflammation Associated With Responsiveness Of Thementioning
confidence: 98%
“…In the context of destroyed lung parenchyma, the load that counteracts the shortening of ASM is depressed and this favors maximal airway narrowing. In this respect, one should focus on the reactivity (the slope of the dose-response curve), which in COPD has been demonstrated to depend on the reduction of FEV 1 (Verhoeven et al 2000) and on airway wall thickness (Corsico et al 2003). The maximal response on the dose-response curve describes a condition of increased risk of severe bronchoconstriction.…”
Section: Clinical Relevance Of Ahr In Copdmentioning
confidence: 99%
“…In this study, the authors recruited subjects with α 1 -antitrypsin deficiency and no current history of smoking, and found a close relationship between the degree of parenchymal destruction and the maximal airway narrowing. On the other hand, plateaus in the dose-response curve have been documented in some individuals with COPD (Verhoeven et al 2000). It can, however, be theorized that, given the structural alterations of the lung parenchyma, higher reactivity is likely to occur in COPD subjects.…”
Section: Clinical Relevance Of Ahr In Copdmentioning
confidence: 99%